MENTORING AND NEW EMPLOYEE SOCIALIZATION: IS IT TIME TO THINK ABOUT MENTOR SELECTION? - Žukauskaitė, Irena (Acta Paedagogica Vilnensia, 2014)
The aim of the study was to analyse the characteristics of employees who become mentors, and to discover how these characteristics are related to new employee socialization. 180 newly recruited employees (56 had mentors and 124 had no mentors), having their trial period in an organization and 56 mentors took part in the study. In order to analyse the aspects of socialization, new employees had to fill the questionnaires evaluating: 1) the amount of different information (Morrison, 1995); 2) job-related state anxiety (Spielberger et al., 1983); 3) the feeling of insider (old-timer); 4) perceived professional competency; 5) attitudes towards the job and towards the organization. Mentors had to fill in questionnaires which measure: 1) professional, social, and andragogical competencies; 2) organizational commitment (O’Reilly, Chatman, 1986); 3) job satisfaction; 4) work motivation; 5) motives of mentoring and experience.The results show that workers who become mentors of new employees are motivated and satisfied with their job, committed to their organization. They demonstrate a good level of professional and social and the average level of andragogical competencies. The usual motives of becoming mentors are seeking of challenges, wish to learn, altruism, the earlier experience of mentorship (being a mentor or a mentee), and financial benefits. Yet there were some mentors who were assigned to new employees without their compliance. The most important qualities of mentors, helping a new employee to socialize, are their professional and social competencies and mentor’s identification with the organization. Moreover, while comparing socialization results of those employees who had no mentors, who had very competent mentors, and who had mentors with lower competencies, it was assumed that sometimes it is better to have no mentor than to have an incompetent one. These results should be taken into consideration by personnel specialists and executives who assign mentors for new employees, because they prove the importance of mentor selection.
Keywords: competencies of mentors; mentor selection; socialization of new employees